Corporate social responsibility and market orientation : an integrated approach towards organizational performance - Muhamad Azrin Nazri; Nor Asiah Omar; Azreen Jihan Mohd Hashim (Penerbit Universiti Kebangsaan Malaysia, 2018)
Takaful operators in countries dominated by Muslim are still experiencing low penetration rate. New emerging customer segments have higher expectation where Takaful operators need more innovative approaches in acquiring and retaining customers. Moreover, Takaful companies need to apply marketing, societal and entrepreneurial concept to make the industry more competitive. Although many Islamic banking and Takaful studies have been conducted, empirical Takaful research is still limited. Therefore, the primary focus of this study is to empirically investigate the influence of market orientation and corporate social responsibility (CSR) towards Takaful agencies’ organizational performance in Malaysia. The first phase of the study involved refinement of CSR measurement items by performing exploratory factor analysis (EFA), where a new dimension was identified. The second phase of study was to test the hypotheses by employing all items adopted from past studies including the refined CSR measures. PLS-SEM analysis involving a two-step approach on 211 valid data shows co-adoption of CSR and market orientation influences organizational performance.